Injury patterns in synchronized skating: A growing and evolving sport - Simunjak, T.; Dubravcic-Simunjak, S.; Abbott, K.; Busac, L. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Data about injuries among synchronized skating athletes are lacking while physical demands in this sport discipline continue to grow. No injury data among junior synchronized skaters exist. The purpose of this study was to investigate the frequency and pattern of injuries in junior and senior synchronized skaters. METHODS: In this descriptive epidemiology study anonymous questionnaires were distributed to synchronized junior and senior skaters. 708 synchronized skaters (393 juniors and 315 seniors) completed the questionnaire. Male skaters were excluded from analysis. RESULTS: Spinal conditions were reported by 148 (37.7%) juniors compared to 149 (47.3%) of senior skaters with statistically significant cumulative incidence (P=0.01); 23% of juniors and 30.2% of senior skaters reported problems with more than one spinal region; 64.4% juniors and 72.1% senior skaters reported at least one non-spinal injury during their synchronized skating career. There were 380 unique injuries reported by junior skaters and 363 by senior skaters. Lower extremity injuries were the most common injuries in both groups of skaters, followed by upper extremity, head and trunk injuries. From all the anatomical regions mentioned, there was only statistically significant difference between the groups in the occurrence of head injuries with senior skaters having 1.9 greater odds ratio to have head injury. CONCLUSIONS: This study presents new data on the current injury pattern seen in synchronized skating since the inclusion of new skills. The number of head injuries and spinal conditions show statistically significant cumulative incidence in senior compared to junior skaters.